2022
DOI: 10.2147/idr.s365220
|View full text |Cite
|
Sign up to set email alerts
|

Typhoid in Pakistan: Challenges, Efforts, and Recommendations

Abstract: Typhoid, and its extra drug resistant form which is highly prevalent Pakistan, is increasing the burden on healthcare through multiple factors. These range from lack of sanitation, the collapsing economy, and poor access to clean drinking water which have made it arduous for the government and various other organizations in containing it. With the COVID-19 pandemic, treatment of typhoid became a challenge as focus was driven towards limiting the COVID-19 spread, and hence preferential use of antibiotics such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…These findings suggest that infection is attributable to short-cycle transmission, which involves direct contamination via the feco-oral pathway. Mobile street vendors and corner stores could play an important role in this context ( 11 , 19 ). They frequently place their carts near drainage systems and overlook essential hygiene procedures, such as handwashing during food preparation and raw goods handling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings suggest that infection is attributable to short-cycle transmission, which involves direct contamination via the feco-oral pathway. Mobile street vendors and corner stores could play an important role in this context ( 11 , 19 ). They frequently place their carts near drainage systems and overlook essential hygiene procedures, such as handwashing during food preparation and raw goods handling.…”
Section: Discussionmentioning
confidence: 99%
“…The differences could be attributed to antibiotic stewardship programs, a well-developed health care infrastructure, and an exceptional surveillance and monitoring system in these countries. In contrast, Pakistan, a country facing economic challenges, can only allocate less than USD $200 million for its entire health care system ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases in Pakistan sharply surged in 2016, following the introduction of a highly drug-resistant (XDR) typhi outbreak in Hyderabad. 16 Typhoid appears to have a seasonal pattern, peaking from July to October after rain, notably in the majority of South Asian and South East Asian countries, perhaps due to floods brought on by heavy rains that contaminate drinking water sources with sewage. 17 Per this, a study conducted in Karachi showed a prevalence of serologically positive patients at 20.13% in the summer and 17% in the winter.…”
Section: Water-borne Diseasesmentioning
confidence: 99%